ANALYSIS OF EV ADOPTION IN INDONESIA FOLLOWING THE WITHDRAWAL OF INCENTIVES USING DYNAMIC SYSTEM SIMULATION - Prabaswara, Amsal Haria; Pambudi Tama, Ishardita; Eunike, Agustina (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2026)
The withdrawal of electric vehicle (EV) incentives in Indonesia in early 2026 has raised concerns over achieving the national adoption target of 2 million units by 2030. This study develops a system dynamics model to project EV adoption following the incentive withdrawal, incorporating key factors such as charging time, economic attractiveness, driving range, and charging infrastructure availability. The model, constructed using Vensim PLE, consists of a Causal Loop Diagram and a Stock-and-Flow Diagram, validated through dimensional-consistency, extreme-condition, and behaviour-reproduction test. Simulations of four scenarios from 2026 to 2035 reveal that combining fiscal incentives with charging infrastructure expansion (Scenario 3) yields the highest EV volume, annual sales, attractiveness, and number of charging stations. However, none of the scenarios achieve the 2 million target by 2030; Scenario 3 reaches it in 2033, one year earlier than the base run. These findings underscore the need for simultaneous fiscal and infrastructural support to accelerate EV adoption in Indonesia.